IDENTIFICATION OF A MAJOR QUANTITATIVE TRAIT LOCUS CONFERRING RICE BLAST RESISTANCE USING RECOMBINANT INBRED LINES - Sobrizal, Sobrizal; Bustamam, Masdiar; Carkum, Carkum; Warsun, Ahmad; Human, Soeranto; Fukuta, Yoshimichi (Indonesian Journal of Agricultural Science, 2010)
Blast disease caused by Pyricularia oryzae is one of the limitingfactors for rice production world wide. The use of resistantvarieties for managing blast disease is considered as the mosteco-friendly approaches. However, their resistances may bebroken down within a few years due to the appearance of newvirulent blast races in the field. The objective of the presentstudy was to identify the quantitative trait locus (QTL) conferringresistance to blast disease using 126 recombinant inbred(RI) lines originated from a crossing of a durably resistant uplandrice genotype (Laka) and a highly susceptible rice accessioncultivar (Kencana Bali). The RI population was developedthrough a single seed descent method from 1997 to 2004.Resistance of the RI lines was evaluated for blast in an endemicarea of Sukabumi, West Java, in 2005. Disease intensity of theblast was examined following the standard evaluation systemdeveloped by the International Rice Research Institute (IRRI).At the same year the RI lines were analyzed with 134 DNAmarkers. Results of the study showed that one major QTL wasfound to be associated with blast resistance, and this QTL waslocated near RM2136 marker on the long arm of chromosome11. This QTL explained 87% of the phenotypic variation with37% additive effect. The map position of this QTL differedfrom that of a partial resistant gene, Pi34, identified previouslyon chromosome 11 in the Japanese durably resistant variety,Chubu 32. The QTL, however, was almost at the same positionas that of the multiple allele-resistant gene, Pik. Therefore, anallelic test should be conducted to clarify the allelic relationshipbetween QTL identified in this study and the Pik. The RI linesare the permanent segregating population that could be veryuseful for analysing phenotypic variations of important agronomictraits possibly owned by the RI lines. The major QTLidentified in this study could be used as a genetic resource inimprovement of rice varieties for blast resistance in Indonesia